Moral values and moral identity moderate the indirect relationship between sport supplement use and doping use via sport supplement beliefs - Hurst, P.; Ring, C.; Kavussanu, M. (Journal of Sports Sciences, 2022)
The Incremental Model of Doping Behaviour suggests doping grows out of the habitual use of performance-enhancing methods (e.g., sport supplements) and belief that they are necessary for performance. Importantly, in this model, doping is viewed as functional rather than moral choice. In two studies, we examined whether sport supplement use was indirectly related to doping use via sport supplement beliefs, and whether personal morality moderated this relationship. Competitive athletes (Study 1, N = 366; Study 2, N = 200) completed measures of supplement use, beliefs, and doping use. They also completed measures of moral values (Study 1) and moral identity (Study 2). In both studies, supplement use was indirectly related to doping use via beliefs. Moreover, this indirect relationship was moderated by moral values (Study 1) and moral identity (Study 2). That is, the relationship between supplement use and doping use via beliefs was negated when moral values and moral identity were high but not when they were low or moderate. Taken together, our findings suggest that sport supplement users, who believe they are necessary, are more likely to dope if they have low moral values and believe that being a moral person is unimportant to their self-image.